Metody konstrukcji planów eksperymentów z wykorzystaniem standardowych i zmodyfikowanych tablic ortogonalnych Taguchiego - Peternek, Piotr (Method of construction of experimental plans with standard and modified Taguchi's orthogonal arrays, 2006)
The article discusses the problem of construction of experimental plans. The author presents the method proposed by Taguchi in which problem of choosing a plan is connected with the indication of proper orthogonal array. Detailed algorithm of construction of plans with the methods of modifycations of orthogonal arrays essential in some cases is presented in article. The results of such modifications in orthogonal array are discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1105, s. 111-126